Impacto del programa de incentivos municipales en la reducción de la anemia del distrito El Tigre 2020 - 2021 - Meoño Zavaleta, Héctor Manuel (2022)
The present investigation had as objective: To determine the impact of the municipal incentive program in the reduction of anemia in the district of El Tigre 2020-2021, for which a study of applied type, explanatory level and non-experimental design has been chosen, it was taken Taking into account the relevant documentation on the incentive program and the reduction of anemia, provided by the district municipality and the health center, respectively, the technique used was the collection of information through documentary analysis and the registration form as an instrument. of data, which allowed us to systematize and analyze information from said documents. Therefore, the investigation concludes that the fulfillment of goals 4 and 5 of the municipal incentive program is optimal, in addition funds were allocated in favor of the district for the fulfillment of the 2020 goals, as well as the rate of anemia in children and girls from 3 to 11 months, presents a significant reduction with respect to the anemia index in 2021 after being benefited by the municipal incentive program. Finally, it has been possible to determine that the impact of the municipal incentive program on the reduction of anemia in the district of El Tigre 2021, in such a way that the impact has a bilateral significance of 0.028 with respect to the student's t-test.